Implementation of the Al-Miftah Li Al-‘Ulum Method in Kitab Kuning Learning at Megamendung Agrocultural Islamic Boarding School - Syahdheria Ferrary; Yal Robiansyah; Tia Putri Pratiwi; Dania Dania (Jurnal Cendekia Ihya, 2026)
This study aims to describe the implementation of the Al-Miftah Li Al-‘Ulum method in the learning of kitab kuning and to analyze the obstacles as well as teachers’ efforts in improving students’ reading ability. The research was conducted at Pesantren Alam Agrokultural Megamendung Bogor, focusing on first-grade ibtida’iyyah students. The learning material was the kitab Akhlak Lil Banin, with emphasis on the reading indicator of mastering syakal/harakat. This study employed a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research subjects consisted of seven informants, including two teachers and five students, selected using purposive sampling. Data validity was ensured through source and technique triangulation. The findings show that the implementation of the Al-Miftah Li Al-‘Ulum method has not been fully optimal due to internal and external obstacles. Internal obstacles include low student motivation, a tight pesantren schedule, and a lack of teacher appreciation after students succeed in reading the text. External obstacles involve limited learning time, leading students to request additional hours. Teachers’ efforts to overcome these obstacles include providing extra learning sessions, strengthening nahwu material, assigning reading tasks before and after lessons, and giving additional assignments outside the classroom.